Privacy, Security, and Ethics in Technology: A Qur'anic Perspective Through Cybercrime - Aisyah, Septi; Ainur Rhain (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2025)
The rapid advancement of technology facilitates all forms of human activities, especially in communicating. But not a few who use technology inappropriately, such as making technology a means to steal, spread lies, hate speech and various modes of fraud. Such as making technology a means to steal, spread lies, hate speech and various modes of fraud. This research uses literature research methods with a maudhui approach according to Al-Farmawi. Studies show that in the Qur'an there are guarantees of security, privacy, and ethics regarding the use of technology. Thus, it can be proven that the Qur'an can indeed be used as a reference to solve contemporary problems that exist today, including the problem of crime in cyberspace.